The ecotoxicity and tribological properties of choline monocarboxylate ionic liquid lubricants. (30th August 2019) - Fan, Mingjin; Zhang, Shuai; Ma, Lin; Lu, Yu; Ai, Jia; Du, Xin; Sun, Wenjing; Yang, Desuo; Zhou, Feng; Liu, Weiming
Abstract: In this work, a series choline monocarboxylate ionic liquids ([Ch][MA] ILs) were synthesized. The physicochemical properties and lubricating efficiency of the ILs on copper and aluminum discs were systematically investigated. At the same time, their ecotoxicity was explored on aquatic organisms. In comparison with 1‐butyl‐3‐methyl imidazolium tetrafluoroborate (L‐B104), which is a kind of traditional IL, [Ch][MA] ILs exhibited excellent lubricating properties and low toxicities, thus can be considered as environmentally friendly lubricants in tribology.